Job characteristics and perceived organizational support among police officers - Reynolds, Paul (Criminology, criminal justice, law & society, 2018)
Research supports that treatment of employees, in terms of organizational policies, practices, and resources, are associated with employees’ perception of organizational support. Furthermore, research supports that there is often disparate treatment between employees’ work related factors. For this reason, it is reasonable to speculate that variances in police officers’ perception that their organization cares about them and values their work contributions may exist. The purpose of this exploratory research was to describe how police officers’ job characteristics (duty assignment, rank, tenure, and department size) might be associated with perceptions of organizational support. Utilizing OLS regression, the findings revealed that perceived organizational support varied across different job characteristics. This study extends our understanding of how the aforementioned job characteristics are associated with police officer attitudes